The Crisis in Lithospheric Research - Hoffman, Paul (Geoscience Canada)

(untitled) (The Geological Association of Canada, 1993)
Abstract Lithospheric research faces a crisis. Mineral and hydrocarbon exploration (the fiscal rationale for such research) have decreased, and job prospects and undergraduate student enrollments are down. The declines are thought to be asting. Concurrently, growing environmental concerns have been a boon for funding in hydrology and the ocean, atmosphere and climate sciences. Among the environmental concerns most likely (for proper political and economic reasons) to spawn durable action are the remediation of waste dumps and the treatment of their leachates. This will require and also contribute to a greatly enhanced understanding of the physics, organic and inorganic chemistry, and geology of groundwater flow in the upper lithosphère. The knowledge gained will pay dividends in the eventual exploitation of the large portion of hydrocarbons remaining in the ground after conventional extraction. We should, therefore, expect that the emphasis inlithospheric research, which since the mobilist revolution has focussed on deep-seated processes, will shift in the direction of processes that operate from the top down. The scale and duration of groundwater migration, its control by tectonically induced topography and subsurface geological structure, and the estimated flow velocities equal to those of fast-moving lithosphericplates ensure the continuing importance of research directed at processes operating on geological time-scales.